TAMAN BERMAIN HIJAU: STRATEGI PEMBARUAN FASILITAS BERMAIN ANAK MENUJU LINGKUNGAN YANG RAMAH DAN KREATIF DI RPTRA PETUKANGAN BERSERI - Widi Wahyudi; Aris Wahyu Kuncoro; Hasan Ipmawan; Koen Hendrawan; Pambuko Naryoto; Marini Marini (Jurnal Padamu Negeri, 2024)
The Community Engagement in the Green Playground initiative aims to revitalize children's play facilities in RPTRA Petukangan Berseri with an emphasis on creating a friendly and creative environment. The strategy employed integrates the Green Playground concept, encompassing the use of eco-friendly materials, inclusive facility designs, and the expansion of green open spaces. With active participation from the local community, this program has yielded significant positive impacts.A crucial aspect of this initiative is the physical renovation of children's play facilities at RPTRA Petukangan Berseri. Through the Green Playground concept, these facilities are refurbished with more inviting and safe designs, fostering an engaging and secure play environment for children. Emphasizing the use of eco-friendly materials also provides long-term benefits to the surrounding environment, reducing carbon footprints and enhancing ecological sustainability. The implementation of the Green Playground concept offers opportunities for children and parents to learn about the importance of environmental conservation and practice sustainable lifestyles. Consequently, this program not only delivers tangible physical benefits but also enhances awareness and environmental responsibility at the local level.The success of the Community Engagement in the Green Playground initiative at RPTRA Petukangan Berseri serves as an inspirational example for sustainable development efforts in various cities and regions. Moreover, it makes a significant positive contribution to the well-being of children and their living environment.